2017
DOI: 10.1007/s10548-017-0555-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered Effective Connectivity Network in Childhood Absence Epilepsy: A Multi-frequency MEG Study

Abstract: Using multi-frequency magnetoencephalography (MEG) data, we investigated whether the effective connectivity (EC) network of patients with childhood absence epilepsy (CAE) is altered during the inter-ictal period in comparison with healthy controls. MEG data from 13 untreated CAE patients and 10 healthy controls were recorded. Correlation analysis and Granger causality analysis were used to construct an EC network at the source level in eight frequency bands. Alterations in the spatial pattern and topology of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 50 publications
4
37
0
Order By: Relevance
“…Recent years have also witnessed great advances in neuroimaging modalities such as magneto-and electroencephalography (MEG/EEG), functional magnetic resonance imaging (fMRI), and diffusion tensor imaging (DTI), which provide valuable tools for the identification of networks (Teipel et al, 2009Ciuciu et al, 2014Bönstrup et al, 2015;Wu et al, 2017;Dimitriadis et al, 2018). Among the multimodal neuroimaging techniques, EEG may have some major assets from a clinical perspective since it is non-invasive, inexpensive, and easy to use (Fan and Chou, 2018;Jacobs et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have also witnessed great advances in neuroimaging modalities such as magneto-and electroencephalography (MEG/EEG), functional magnetic resonance imaging (fMRI), and diffusion tensor imaging (DTI), which provide valuable tools for the identification of networks (Teipel et al, 2009Ciuciu et al, 2014Bönstrup et al, 2015;Wu et al, 2017;Dimitriadis et al, 2018). Among the multimodal neuroimaging techniques, EEG may have some major assets from a clinical perspective since it is non-invasive, inexpensive, and easy to use (Fan and Chou, 2018;Jacobs et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations of resting-state network in the frontal lobe cortex were also reported in studies on AE [46]. Besides, a multi-frequency MEG study [47] showed that CAE patients displayed frequencyspecific abnormalities in the network pattern even during the inter-ictal period, and the frontal cortex and precuneus/posterior cingulate cortex might play crucial roles in the pathophysiology of CAE. The effective connectivity network of CAE patients was overconnective and random during the inter-ictal period.…”
Section: Reviewmentioning
confidence: 59%
“…In a study specifically examining connectivity changes during the start of seizures, seizures were associated with an increase in the power of delta frequency activity on MEG recordings . This was the same frequency band driving the increased short‐range frontal lobe connectivity during interictal recordings described above . Thus, this might represent another case of transient epileptiform activity inducing persistent connectivity changes.…”
Section: Childhood Absence Epilepsymentioning
confidence: 88%
“…73 This was the same frequency band driving the increased short-range frontal lobe connectivity during interictal recordings described above. 69 Thus, this might represent another case of transient epileptiform activity inducing persistent connectivity changes.…”
Section: Executive Functioning and The Frontal Lobementioning
confidence: 99%
See 1 more Smart Citation